The Network of Law Reviews: Citation Cartels, Scientific Communities, and Journal Rankings. - Perez, Oren; Bar‐Ilan, Judit; Cohen, Reuven; Schreiber, Nir (Modern Law Review, 2019)
Research evaluation is increasingly influenced by quantitative data. We focus on the influential Web of Science Journal Citation Reports (JCR) ranking of law journals and critically assess its methodology. In particular, we consider the existence and impact of a tacit citation cartel between US law reviews. A study of 45 US student‐edited (SE) and 45 peer‐reviewed (PR) journals included in the category of Law in the JCR revealed that PR and SE journals are more inclined to cite members of their own class and that this phenomenon is more pronounced in SE generalist journals, reflecting tacit cartelistic behavior generated by deeply entrenched institutional practices. Because US SE journals produce more citations than PR journals, the fact that their citations are directed almost exclusively to SE journals elevates their scores and distorts the journals' ranking and can consequently undermine the flow and creation of ideas. We discuss policy measures that can counter the adverse effects of this situation.